2020
DOI: 10.1186/s12889-020-09258-4
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation of nationwide screening of pregnant women for HTLV-1 infection in Japan: analysis of a repeated cross-sectional study

Abstract: Background: Screening of pregnant women carrying human T-lymphotropic virus type 1 (HTLV-1) has a crucial role in reducing the number of HTLV-1 carriers. A national HTLV-1 screening program for pregnant women was started in 2011 in Japan. The purpose of this study is to report on the implementation of this nationwide screening program. Methods: This was a retrospective repeated cross-sectional study. We used datasets from surveys of HTLV-1antibody-positive pregnant women performed by the Japan Association of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…When a pregnant woman is identified as a carrier, the healthcare provider explains the risk of MTCT and preventive measures as much as possible before delivery. Our retrospective surveys conducted in 2011, 2013, and 2016 confirmed that a nationwide screening program for HTLV-1 was almost fully implemented in Japan [34]. Even if a child is born to a carrier pregnant woman, a regular infant's health check-up schedule is appropriate unless the mother is highly anxious.…”
Section: Screening Program In Japanmentioning
confidence: 55%
“…When a pregnant woman is identified as a carrier, the healthcare provider explains the risk of MTCT and preventive measures as much as possible before delivery. Our retrospective surveys conducted in 2011, 2013, and 2016 confirmed that a nationwide screening program for HTLV-1 was almost fully implemented in Japan [34]. Even if a child is born to a carrier pregnant woman, a regular infant's health check-up schedule is appropriate unless the mother is highly anxious.…”
Section: Screening Program In Japanmentioning
confidence: 55%
“…The ATL Prevention Program in Nagasaki from 1987 to 2004 revealed a marked reduction of HTLV-1 mother-to-child transmission by withholding breastfeeding for carrier mothers and has recommended avoiding breastfeeding as the most reliable method for mother-to-child transmission prevention [17]. Japan is the first and only country in the world that has implemented nationwide HTLV-1 antenatal screening since 2011 to prevent mother-to-child transmission of HTLV-1 infection [18]. Withholding breastfeeding for mothers with positive HTLV-1 antibody tests at HTLV-1 antenatal screening can reduce the rate of mother-to-child transmission of HTLV-1 from 20.3% for long-term breastfeeding (≧6 months) and 7.4% for short-term breastfeeding (<6 months) down to 2.5% [7].…”
Section: Introductionmentioning
confidence: 99%
“…3 A nationwide HTLV-1 screening program for pregnant women started in 2011, and provision of information to HTLV-1 careers has been systematized in Japan. 4 However, there is little information on pregnancy and childbirth of patients with HAM/TSP developed from HTLV-1 carriers. 5 There are more female patients with HAM than male patients, and several medical articles mentioned about early juvenile HAM/TSP.…”
Section: Introductionmentioning
confidence: 99%
“…The average age of onset is recorded around 50 years 3 . A nationwide HTLV‐1 screening program for pregnant women started in 2011, and provision of information to HTLV‐1 careers has been systematized in Japan 4 . However, there is little information on pregnancy and childbirth of patients with HAM/TSP developed from HTLV‐1 carriers 5 …”
Section: Introductionmentioning
confidence: 99%